A Rare Case Of Duodenal Metastases From Hepatocellular Carcinoma - Affirul Chairil Ariffin; Azrin Waheedy Ahmad; Zamri Zuhdi; Azlanuddin Azman; Hairol Othman; Razman Jarmin (Amcricas Hcpato-Pancrcato-Biliary Association, 2024)
Introduction: Hepatocellular carcinoma (HCC) is the commonest primary tumor in the liver. It has been shown to have a strong association with hepatitis B and C. HCC not only commonly metastases to the other part of the liver but also commonly metastases to the lung. Involvements of upper gastrointestinal organs are rare. We report a case of hepatocellular carcinoma with duodenal metastases. Method: A 58 years old Chinese man with a background history of hepatitis B presented with right hypochondrium pain. No jaundice or any constitutional symptoms noted. Physical exams revealed irregular right hypochondrium mass. No ascites palpable. Most blood investigation was unremarkable except for a raised Alpha fetoprotein of 2920. Imaging studies confirmed a diagnosis of a segment 4B HCC with enlarged portal nodes and left portal vein thrombosis. Despite his Childs score A, he was deemed inoperable and subjected to chemoembolization. During a subsequent follow up, he developed symptomatic anaemia with hemoglobin level of 6.2 g/dl. He developed multiple episodes of anaemia and Upper GI endoscopy shows a bleeding tumor at first part of duodenum extending to the second. Biopsy revealed as metastatic HCC. Results: Conclusions: Hepatocellular carcinoma is known to spread via haematogenous, lymphatics or trancoelomic. The usual sites of metastases are lung, regional lymph nodes and bones. Metastases via direct spread are uncommon hence the rarity of metastases to other upper gastrointestinal organs especially small bowel. This presentation imposed a treatment dilemma due to the limited approach to both primary and the metastases lesion.